PENDEKATAN LOGOTERAPI VIKTOR FRANKL DALAM KONSELING KELUARGA DI MASA KRISIS - Felix Trisuko Nugroho (ADIBA : JOURNAL OF EDUCATION, 2025)
Viktor E. Frankl believes that the key for a person to survive and live in times of crisis is to find and have a good meaning in life. However, when squeezed by difficult conditions such as the loss of a family member due effect of broken home, not everyone can find the right meaning in life, so they need professional help from a counselor to be able to find meaningful meaning in life. Therefore, this paper aims to describe Viktor E. Frankl's counseling approach regarding the meaning of life and its relevance in the current crisis. Using the literature review method on various sources (articles and scientific books) related to the topic of discussion. This research found that to help troubled individuals (depressed, anxious, useless) due to loss of meaning in life during the current crisis, a counselor can use individual counseling with the Viktor E. Frankl logotherapy approach with the help of several techniques such as paradoxical intention, dereflection, questions Socrates.